Ideology, affect, semiotics: towards a non-personal theory of personality. - Larocco, Steve (Integrative psychological & behavioral science, 2014)
Personality theories, as Giordano (2014) argues, often treat Western versions of the self as having universal import. Eastern notions of self, however, offer a dramatically different basis for thinking about what personality might be. This paper, nonetheless, seeks to offer a general framework for theorizing about the epiphenomenon of personality in any culture, asserting that it is an effect of specific histories of ideological practices, semiotic networks and systems, and affect, which engage each other in dialogic and dialectical ways. The interactions of these factors, guided by ideology, regularize behavior and affective dynamics, largely in non-personal ways. Subjects are produced and reproduced from these complex interactions, which are situationally specific and simultaneously transpersonal. The subjects formed through these interactions are the basis for the folk psychology of personality, which treats the transient, varying effects of these interactions as more or less reified qualities that form a basis for the construction of selfhood, however conceived.
3 citations (Crossref) [2023-10-31] Place: United States Larocco, Steve. Southern Connecticut State University, New Haven, CT, USA, laroccos1@southernct.edu.
Keywords: *Affect; *Culture; *Personality; *Psychological Theory; Affect; Culture; Five-Factor Model; Humans; Ideology; Personality; Psychological Theory; Semiotics; affect; cultural anthropology; dept.eng; human; personality; psychological theory